2019
DOI: 10.1016/j.ebiom.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PIMREG promotes breast cancer aggressiveness via constitutive activation of NF-κB signaling

Abstract: Background It is well-established that activation of nuclear factor-kappa B (NF-κB) signaling plays important roles in cancer development and progression. However, the underlying mechanism by which the NF-κB pathway is constitutively activated in cancer remains largely unclear. The present study aimed to investigate the effect of PICALM interacting mitotic regulator (PIMREG) on sustaining NF-κB activation in breast cancer. Methods The underlying mechanisms in which PIMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 39 publications
4
36
0
5
Order By: Relevance
“…Overexpression of FAM64A was reported in leukemia, lymphoma and several types of solid cancer [ 46 ]. In breast cancer, overexpression of FAM64A enhanced the transactivation of NF-κB by disrupting the NF-κB/IκBα negative feedback loop [ 47 ]. Another study demonstrated that FAM64A regulates STAT3 activation and is involved in Th17 differentiation, colitis and colorectal cancer development [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of FAM64A was reported in leukemia, lymphoma and several types of solid cancer [ 46 ]. In breast cancer, overexpression of FAM64A enhanced the transactivation of NF-κB by disrupting the NF-κB/IκBα negative feedback loop [ 47 ]. Another study demonstrated that FAM64A regulates STAT3 activation and is involved in Th17 differentiation, colitis and colorectal cancer development [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The release of pro-and anti-inflammatory cytokines has a significant role in the triggering of malignant transformation and display of stem cell properties [32][33][34] Gene profiling has yielded important mechanistic insights into the role of PDGFB signaling in RASSF1A-mediated stem cell plasticity. The PDGFB protein encoded by the PDGFB gene in humans is a member of the platelet-derived growth factor family that can be released into the microenvironment as a homodimer (PDGF-BB) or as a heterodimer with the platelet-derived growth factor alpha (PDGFA) polypeptide (PDGF-AB).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the RNAs have been reported in the previous study. PICALM interacting mitotic regulator (PIMREG) could promote breast cancer aggressiveness via sustaining nuclear factor (NF)-κB activation ( Jiang et al, 2019 ). Progestin and adipoQ receptor family member (PAQR) 4 has been found to compete with S-phase kinase-associated protein (SKP) 2 for binding to the same region in cyclin-dependent kinase (CDK) 4, thereby abrogating SKP2-mediated ubiquitination of CDK4 and contributing to tumorigenesis ( Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%